The Circle of Reason - Ghosh, Amitav (Haryana : Penguin, 2008)
In a vivid and magical story, this novel traces the misadventures of Alu, a young master weaver in a small Bengali village who is falsely accused of terrorism. Alu flees his home, traveling through Bombay to the Persian Gulf to North Africa with a bird-watching policeman in pursuit.
Keywords: English Fiction; Terrorism -- Prevention; Fugitives from justice; False testimony